Manajemen Smart Library dalam Peningkatan Minat Literasi Peserta Didik (Studi Kasus di SDN Model Kota Malang) - Mubarika, Felisa Dwi; Sultoni, Sultoni; Benty, Djum Djum Noor; Imron, Ali (Universitas Negeri Malang, 2025)
This article aims to describe the profile of the smart library at SDN Model Kota Malang, outline the management of the smart library, and identify both the supporting and hindering factors that are consistently managed by SDN Model Kota Malang to enhance students' literacy interest. This research employs a qualitative case study method, focusing on key informants including the library head, smart library coordinator, homeroom teachers, and students. The findings reveal a deeper understanding of the smart library’s profile, its members, achievements, and the collaborations established within the library. Additionally, it further uncovers the management strategies of the smart library in promoting students' literacy interest, as well as a deeper insight into the supporting and hindering factors present in the management of the smart library. The conclusion of this research indicates that the smart library is a facility with numerous programs aimed at enhancing the literacy interest of students at SDN Model Kota Malang, especially in light of the increasing trend of students moving away from libraries due to the rapidly advancing digital era